High‐Voltage and Fast‐Charge Electrolytes for Lithium‐Ion Batteries. Issue 11 (10th October 2022) - Wan, Shuang; Ma, Weiting; Xiao, Ying; Chen, Shimou
Abstract: Lithium‐ion batteries (LIBs) with high energy density and fast‐charge capability are urgently required for the ever‐growing demands for electric vehicles and hybrid electric vehicles. To achieve this demand, as one of the important components, electrolytes are required to work well at a high voltage to fulfill the good performance of high energy density batteries and facilitate the fast‐charge process. In this review, we mainly focus on the electrolytes design for LIBs under high‐voltage and fast‐charge conditions. The bottlenecks and the typical resolving strategies referring to lithium salts, solvents, solid electrolyte interface, additives and solvent structures in electrolytes are presented in detail. Finally, we propose the challenges regarding electrolytes design insight and inspiration for LIBs under the two conditions to give a better guide for the rationale design of the high energy density and fast‐charge devices in the future applications. Abstract : Towards application : In this review, we mainly focus on the electrolytes design for LIBs under high‐voltage and fast‐charge conditions. The bottlenecks and the typical strategies referring to lithium salts, solvents, solid electrolyte interface, additives and solvent structures in electrolytes are presented in detail.